Plant Stress-Tolerance Traits Predict Salt Marsh Vegetation Patterning - Veldhuis, Erik R.; Schrama, Maarten; Staal, Marten; Elzenga, J. Theo M. (Frontiers in Marine Science, 2019)
It is increasingly acknowledged that stresses can resonate across the boundaries between ecosystems. Salt marshes, vast areas shaped by ocean-shore interactions, constitute prime examples of ecosystems where multiple stress factors arising from one ecosystem act on the local community of another ecosystem. Although it is generally recognized that zonation of plant communities on salt marshes is strongly affected by marine stress factors associated with frequent flooding (salinity, anoxia), it is largely unknown what the isolated and interacting effect are of these different stresses. This calls for experiments to disentangle the relative effects of these single and interacting multiple stresses. In this study, we determined the single and interacting effects of two main abiotic stress factors on salt marshes: salinity and anoxia (as a result of flooding) and one biotic stress factor: soil compaction (as a result of livestock grazing) on the growth of the twelve dominant salt marsh plant species, using a full-factorial experiment. To link the experimental work to distributions of natural plant communities along a natural stress gradient, we related our experimental results to observed plant species distributions on a salt marsh that is exposed to all these three stresses. Whereas salinity strongly affected ten species with two high-marsh species not surviving the highest salinity levels whereas anoxia only consistently affected growth of four species. Interestingly, we observed no synergistic effect of anoxia and salinity in salt marsh plants. Moreover, we observed a trade-off between the amount of aerenchyma and mechanical strength, indicating that species vary in their resistance to soil compaction. Overall, our results suggest that salinity is a major determinant of plant species composition on the salt marsh, followed by anoxia. The importance of soil compaction depends on salt marsh elevation: on the low marsh, increased oxygen supply by aerenchyma seems to outweigh resistance against mechanical stress whereas on the anaerobe low marsh, the reverse applies. Using the experimental data to predict cover of plant species in the field, our results suggest that the combination of plant responses to the various stresses may be a powerful predictor for explaining the plant composition on the salt marsh.